Unusual Presentation of Polyarteritis Nodosa (Pulse, 2014)
Polyarteritis Nodosa (PAN) is a multisystem, necrotizing vasculitis of small and medium-sized muscular arteries. Sometimes PAN is detected at cholecystectomy or appendectomy in the absence of other disease manifestations. In such cases, surgical removal of the involved organ may be curative. Here we presented a case of poly arteritis nodosa, the process of diagnosis and explained the pathophysiology of the disorder and currently available treatments DOI: http://dx.doi.org/10.3329/pulse.v5i1.20188 Pulse Vol.5 January 2011 p.35-38